2023
DOI: 10.1007/s10096-023-04601-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and antimicrobial resistance profile of Neisseria gonorrhoeae in Catalonia, Spain, 2016–2019

Mercè Herrero,
Sonia Broner,
Adrià Cruells
et al.

Abstract: Antimicrobial resistance data for Neisseria gonorrhoeae is globally sparse and resistant strains are emerging in Catalonia. We aim to describe epidemiological and antimicrobial resistance in all patients infected with N. gonorrhoeae during the period from 2016 to 2019, using available antimicrobial susceptibility data. We retrospectively analysed confirmed N. gonorrhoeae cases notified to Catalonia’s microbiological reporting system. Antibiotic susceptibility testing (azithromycin, cefixime, ceftriaxone, cipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In our study, all isolates of N. gonorrhoeae remained susceptible to ceftriaxone which is different from other reports that showed resistance from Thailand 17 and Spain. 33 Hence, high multidrug resistant isolates of N. gonorrhoeae were observed in the study area.…”
Section: Discussionmentioning
confidence: 88%
“…In our study, all isolates of N. gonorrhoeae remained susceptible to ceftriaxone which is different from other reports that showed resistance from Thailand 17 and Spain. 33 Hence, high multidrug resistant isolates of N. gonorrhoeae were observed in the study area.…”
Section: Discussionmentioning
confidence: 88%
“…Referring to Italy in 2018, the surveillance system found <0.1% of Ng with CRO-R/DS, 5% to 29.9% with AZM-R, and 30% to 69.9% with CIP-R 7,8 . Focusing on the European region, previous studies suggested an increase in azithromycin resistance, with very limited cases of ceftriaxone resistance 9–11 . Limited data on Ng antimicrobial resistance profile in Italy over the years are available.…”
mentioning
confidence: 99%